2011
DOI: 10.1002/pd.2766
|View full text |Cite
|
Sign up to set email alerts
|

The development of a rapid assay for prenatal testing of common aneuploidies and microdeletion syndromes

Abstract: Objective To develop a novel, rapid prenatal assay for pregnancies with high likelihood of normal karyotypes, using BACs‐on‐Beads™ technology, a suspension array‐based multiplex assay that employs Luminex® xMAP® technology, for the detection of gains and losses in chromosomal DNA. Methods Fifteen relatively common microdeletions were selected that are not detectable, or may be missed, by karyotyping and usually do not present with abnormal ultrasound findings. Chromosomes 13, 18, 21, X, and Y were included. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 24 publications
(27 reference statements)
0
58
1
Order By: Relevance
“…This rapid targeted assay is dependent on DNA extraction and does not require live or intact cells, and represents an interesting alternative to conventional cytogenetics that require cell culture. [5,9,11,12] In our study, cell culture failure prevented standard karyotype analysis of 38 samples. However, Prenatal BoBs TM provided a conclusive result in all cases, making it a useful tool for the cytogenetic analysis of POCs, especially when culture fails.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This rapid targeted assay is dependent on DNA extraction and does not require live or intact cells, and represents an interesting alternative to conventional cytogenetics that require cell culture. [5,9,11,12] In our study, cell culture failure prevented standard karyotype analysis of 38 samples. However, Prenatal BoBs TM provided a conclusive result in all cases, making it a useful tool for the cytogenetic analysis of POCs, especially when culture fails.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Prenatal BoBs TM can detect mosaicism in fetal tissue at a level of 20 -40% abnormal cells or higher, [9,15] and that MCC in the fetal tissue becomes apparent at a level of 20 -30% of normal female cells. [11] Prenatal BoBs has been described as more informative than rapid FISH and QF-PCR, which screen only frequent aneuploidies. [9] This technique also enabled us to provide rapid results with conclu sive outcomes within 24 hours of receipt of the sample, [5,9,11,12] which is about half the time of fast FISH aneuploidy screening, because it is possible to interpret the profiles of several samples in few minutes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytogenetic techniques that are not dependent on actively growing tissue are becoming more common, including quantitative fluorescence (QF)-PCR (2,3), multiplex ligation-dependent probe amplification (MLPA) (4,5), molecular karyotyping (6) and bacterial artificial chromosomes (BACs)-on-Beads™ (BoBs) (7)(8)(9)(10)(11). Of these techniques, BoBs offers the ability to assess small batch sizes at a relatively low cost with comprehensive coverage of all the chromosome arms, whilst complementing the highly interrogative array-based methods that are used in molecular karyotyping.…”
Section: Introductionmentioning
confidence: 99%